Digital games, developing democracies, and civic engagement: a study of games in Kenya and Nigeria. (October 2020) - Fisher, Jolene
The use of serious games for civic learning and engagement is an area of growing interest. However, research to date has predominately examined such games in established democratic contexts and has primarily focused on the potential of in-game content and game mechanics for achieving learning and behavior change outcomes. This study used in-depth interviews with key developmental stakeholders for two civic-focused games, Haki2 in Kenya and Your Excellency in Nigeria, to further our understanding in two important but understudied areas: the potential for games to facilitate civic learning and engagement outcomes in developing democratic contexts; and the role of game production and dissemination processes in this potential. I argue that these processes provide opportunities for direct civic engagement, participatory learning, and group mobilization relevant to facilitating civic behavior in developing democratic contexts. While this research identifies critical limitations for games used as stand-alone tools to achieve civic learning and engagement outcomes, it also identifies the potential for game production and dissemination to engage communities in democratic deliberation, in identifying relevant civic-issues and solutions, to facilitate community discussion, and to mobilize players around relevant issues.